Determinan Tingkat Pengangguran Terbuka Di Kabupaten/Kota Provinsi Kepulauan Riau - Qausar, Najasyi; Aminda, Renea Shinta (Universitas Pembangunan Nasional Veteran Jakarta, 2022)
Riau Islands Province has a fairly large TPT when compared to other provinces in Indonesia. Even TPT in the Riau Islands Province is seen above TPT at the national level. The high level of open unemployment can have a negative effect on the economy of a country. The problem of TPT in Riau Islands Province is caused by the gross regional domestic product, mean years schooling and the district/city minimum wage. This research aims to determine the effect of regional gross domestic product mean years schooling and the district/city minimum wage on the open unemployment rate in the districts/cities of the Riau Islands Province. The data used in this study were 7 districts/cities in the Riau Islands Province for 10 years, from 2011-2020. This research uses panel data analysis method with the best model is Random Effect Model (REM). The results of the study partially prove that GRDP has a negative and significant effect on TPT, RLS and UMK have a positive and significant effect on TPT. Simultaneously prove that GRDP, RLS and UMK have an effect on TPT.